The Nexus between Gendered Power Relations and Socioeconomic Livelihoods of Female-Headed Households: Evidence from Uganda - Mukundane, Charles Godfrey; Twinamatsiko, Medard; Mureembe, Neema (American Research Journal of Humanities & Social Science (ARJHSS), 2024)
Managing a home is traditionally appreciated as the role-sharing phenomenon between a man and woman with their children at some point. Over time, there has been an evolution of family structure not only here in Uganda but the rest of the world. We have seen a growing number of number of female-headed households, which was not the case in the past. In such scenarios, research findings have emerged pointing out the underlying issues surrounding gendered power relations and socioeconomic livelihoods among female headed households. Whereas most studies have been conducted in most parts of the world, there has been a knowledge gap in the context of Uganda. The present study examined the nexus between gendered power relations and socioeconomic livelihoods of female-headed households with a special focus on the Mbarara district of Southwestern Uganda. The study adopted a cross-sectional research design with a quantitative approach to data collection and analysis. The study surveyed 360 households from six sub-counties and identified 186 respondents who participated in this study, using simple random sampling techniques. Data collection was done using structured questionnaires. Data gathered through these questionnaires was thoroughly checked for completeness, entered into Excel sheets and exported to SPSS version 26 for final analysis. The analysis utilized both descriptive and inferential statistics such as frequencies, per cent, mean, standard deviation, Pearson Correlation and hierarchical regression. The study was cleared by the Uganda National for Science and Technology (UNCST) with registration number SS2293ES. Results from the study show that there is a positive insignificant relationship between gender relations and socioeconomic livelihoods of female-headed households in Mbarara District (r=.126, p<.01). The control variables of Age and level of education were found to contribute a statistically significant explanatory power of 3.4% in explaining socioeconomic livelihoods of female-headed households. The variables entered in the regression model explain an overall 28.4% (AdjR2 = .284) of the variance in socioeconomic livelihoods of female-headed households, implying that the remaining 71.6% is explained by factors not considered in this study. The study concluded that gendered power relations do not predict the socioeconomic livelihoods of female-headed households. The study recommends that there is a need to advocate for improved women's health which predicts their longevity and educational attained, which is found to hold a bearing on the socioeconomic well-being of female-headed households. Future studies need to focus on the influence of socio-demographics on the livelihoods of female-headed households.
Keywords: Gender; Power Relations; Socioeconomic; Livelihoods; Demographic Characteristics